2017
DOI: 10.5897/ajbm2017.8275
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate diversification on firm value in Kenya

Abstract: This study investigates the impact of corporate diversification on the value of firms listed at the Nairobi Securities Exchange (NSE). Panel regression techniques were used as the estimation methods. The overall findings of the study where somewhat mixed. The study finds that industrial diversification reduces firm value, but geographical diversification does not have a significant impact on firm value. When examining each industry individually, the study established that industrial diversification enhanced fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To begin with, financial performance as a dependent variable was measured using the modified Tobin's q formula by (Chung & Pruitt, 1994). Empirically, this indicator had been used by related studies like those by (Phung & Mishra, 2016), (Manyuru et al, 2017) and (Saleh et al, 2017). Secondly, institutional ownership as a predictor variable was measured after the approach by (Saleh et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To begin with, financial performance as a dependent variable was measured using the modified Tobin's q formula by (Chung & Pruitt, 1994). Empirically, this indicator had been used by related studies like those by (Phung & Mishra, 2016), (Manyuru et al, 2017) and (Saleh et al, 2017). Secondly, institutional ownership as a predictor variable was measured after the approach by (Saleh et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to this, corporate diversification has been found to negatively relate to firm performance in Croatia (Pavić & Pervan, 2010) and Vietnam (Phung & Mishra, 2016). Other studies have reported nonlinear relationships (Elango, Ma, & Pope, 2008) while some puts forth no relationship between corporate diversification and firm performance as evident from Pakistan (Iqbal, Hameed, & Qadeer, 2012), Italy, Netherlands (Akpinar & Yigit, 2016) and Kenya (Manyuru, Wachira, & Amata, 2017). From an institutional ownership perspective, there exists a positive link with corporate diversification (Gharbi & Jarboui, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…They provide a real advantage for both the business itself and the state. Indeed, in this way, the state can make certain decisions, acting not only as a guarantor of transactions but also as a tool for regulating the financial stability of acquired and expanding organizations, for the prosperity and growth of the countries' economic system in general (Manyuru et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been referred to as the diversification puzzle in the literature and is yet to be resolved for both academics and business practitioners (Mushtaq Hussain Khan et al 2016, Heathcote and Perri 2013, Statman 2004. While some studies highlighted the financial benefits of diversification strategies for firms (Schommer et al 2019, Bhatia and Thakur 2018, Pandya and Rao 1998, Lang and Stulz 1994, others have criticized different forms and dimensions of these strategies (Peng and Lian 2020, Duho et al 2019, Morris et al 2017, Manyuru et al 2017, Kim and Mathur 2008, Wan 1998. Some scholars have even used the term "di-worsification" (Hobson 2019, Lhabitant and Vicin 2004, Franco 2004 to refer to the situation where this strategy exacerbates firms' financial performance.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Even though a large number of researchers in management, economics and finance disciplines are considerably optimistic about the benefits of diversification (Schommer et al 2019, Bhatia and Thakur 2018, Benito Osorio et al 2012, Pandya and Rao 1998, Lang and Stulz 1994, some other scholars have strongly criticized different forms and dimensions of diversification strategy (Peng and Lian 2020, Duho et al 2019, Morris et al 2017, Manyuru et al 2017, Kim and Mathur 2008, Wan 1998. Diversification is even called "di-worsification" by some literature (Franco L.G.…”
Section: Dominant Theories Underpinning the Diversification Strategy ...mentioning
confidence: 99%